2021
DOI: 10.1128/spectrum.00374-21
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Milk Microbiota: Comparison among Three Different DNA Extraction Protocols To Identify a Better Approach for Bacterial Analysis

Abstract: The advance of high-throughput technologies has increased our knowledge of the world of microorganisms, especially of microbial populations inhabiting living animals. This study provides evidence that milk, as other complex sources, could be critical for generating high-quality DNA for microbiota analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…The profile of the decontaminated milk microbiome data in this study showed that Staphylococcus and Acinetobacter were the predominant taxa, which is in line with previous studies [53][54][55]. However, Bacteroidetes, Corynebacterium, Pseudomonas and Staphylococcus might be overestimated in previous bovine milk microbiome studies [4,17,24,25,53,56], as they were identified as contaminants in our study.…”
Section: Characterization Of the De-contaminated Milk Microbiomesupporting
confidence: 91%
“…The profile of the decontaminated milk microbiome data in this study showed that Staphylococcus and Acinetobacter were the predominant taxa, which is in line with previous studies [53][54][55]. However, Bacteroidetes, Corynebacterium, Pseudomonas and Staphylococcus might be overestimated in previous bovine milk microbiome studies [4,17,24,25,53,56], as they were identified as contaminants in our study.…”
Section: Characterization Of the De-contaminated Milk Microbiomesupporting
confidence: 91%
“…Another issue that makes the bacteria in milk important for healthcare is the potential to carry antimicrobial resistance genes, because antibiotic consumption in animal husbandry can be unconscious in most developing countries [ 47 , 48 ]. Antibiotic resistance is not only a major crisis for non-healthy animals (with mastitis), but also a potential problem for healthy animals.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between cows and microorganisms has traditionally been related to intramammary infections [64]. However, recent metagenomic studies indicate that mammary secretions from clinically healthy quarters may harbor genomic markers for detecting several bacterial groups, the majority of which were not associated with mastitis but were defined as "commensal mammary microbiota" [64,98,99]. Whether disruption of udder microbiota diversity (dysbiosis) plays a role in determining susceptibility to mastitis is still unknown, and little is known about the contributions of various biotic and abiotic factors on the composition of udder microbiota diversity [64,100,101].…”
Section: Relationship Between Genomic Genotypic and Phenotypic Udder ...mentioning
confidence: 99%